1999
DOI: 10.1002/(sici)1098-2752(1999)19:8<364::aid-micr3>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Arterial crush injury causes decrease in tissue perfusion at the level of the microcirculation in skeletal muscle flap

Abstract: This study was designed to evaluate the effects of crush injuries to the feeding arteries of a muscle flap on microcirculatory haemodynamics. Eighteen male Sprague-Dawley rats were divided into three experimental groups for intravital microscopy of the cremaster muscle flap. Group 1 served as control. In group 2 the common iliac artery and in group 3 additionally the lower abdominal aorta was crushed with a Kocher clamp (17.4 N) over 5 min. Microcirculatory parameters (red blood cell velocity, vessel diameter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Krapohl et al [45] showed that a crush injury to the arteries supplying the cremasteric muscle in rats resulted in a significant decrease in skeletal muscle perfusion even though the blood supply though the crushed vessel is maintained and that this may be due to thrombogenic results.…”
Section: Essentials Of Hand Surgerymentioning
confidence: 99%
“…Krapohl et al [45] showed that a crush injury to the arteries supplying the cremasteric muscle in rats resulted in a significant decrease in skeletal muscle perfusion even though the blood supply though the crushed vessel is maintained and that this may be due to thrombogenic results.…”
Section: Essentials Of Hand Surgerymentioning
confidence: 99%
“…199720 , Krapohl und Mitarb. 1998 17 und 199914,15,16 ) sowie bei Ischämie-Reperfusionsreaktionen(Smith und Mitarb. 1989 24 , Siemionow und Mitarb.…”
unclassified